High intrinsic water use efficiency is underpinned by high stomatal aperture and guard cell potassium flux in C3 and C4 grasses grown at glacial CO2 and low light. (28th October 2021) - Israel, Walter Krystler; Watson-Lazowski, Alexander; Chen, Zhong-Hua; Ghannoum, Oula
Abstract: We compared how stomatal morphology and physiology control intrinsic leaf water use efficiency (iWUE) in two C3 and six C4 grasses grown at ambient (400 µmol mol –1 ) or glacial CO2 (180 µmol mol –1 ) and high (1000 µmol m –2 s –1 ) or low light intensity (200 µmol m –2 s –1 ). C4 grasses tended to have higher iWUE and CO2 assimilation rates, and lower stomatal conductance ( g s ), operational stomatal aperture ( a op ), and guard cell K + influx rate relative to C3 grasses, while stomatal size (SS) and stomatal density (SD) did not vary according to the photosynthetic type. Overall, iWUE and g s depended most on a op and density of open stomata. In turn, a op correlated with K + influx, stomatal opening speed on transition to high light, and SS. Species with higher SD had smaller and faster-opening stomata. Although C4 grasses operated with lower g s and a op at ambient CO2, they showed a greater potential to open stomata relative to maximal stomatal conductance ( g max ), indicating heightened stomatal sensitivity and control. We uncovered promising links between a op, g s, iWUE, and K + influx among C4 grasses, and differential K + influx responses of C4 guard cells to low light, revealing molecular targets for improving iWUE in C4 crops. Abstract : Across two C3 and six C4 grasses, intrinsic water use efficiency was strongly associated with stomatal conductance, operational stomatal aperture, guard cell K + influx, and stomatal opening speed on transition to high light.